The Semantic Dimension of the Prophetic Word - Ben Ali, Ben Ahmed; Layla, Zian (Journal of Humanities & Social Sciences, 2018)
This study aims at revealing the problematic relationship between the functions of the structure of language and the significance of the prophetic discourse, in terms of Phonological structure, morphological structure and structural structure, as well as the disclosure of the psychological and social dimensions of the Prophet’s text. Scientists and researchers have interested in the science of semantics and stylistic study of relations between the linguistic component and semantic component in the speech event through scientific approaches based on the grammatical language standards; whether Phonological or morphological or grammatical or lexical, and to highlight the secrets of the linguistic expressions of thoughts and feelings, and the impact of these terms on Recipient receiver. From this point of view we presented this research to highlight the features of distinctive rhetoric, and the manifestations of linguistic creativity in our Prophet Muhammad, in his choice of the appropriate words in his conversations, and the synergy with context and place; for the purpose of alerting and guidance.